Imbalance of Endogenous Hydrogen Sulfide and Homocysteine in Chronic Obstructive Pulmonary Disease Combined with Cardiovascular Disease - He, Yanjing; Liu, Shaoyu; Zhang, Zhe; Liao, Chengcheng; Lin, Fan; Yao, Wanzhen; Chen, Yahong (Frontiers in Pharmacology, 2017)
Background: Considerable studies showed associations between chronic obstructive pulmonary disease (COPD) and cardiovascular disease (CVD), we evaluated the role of endogenous hydrogen sulfide (H2S)/homocysteine (Hcy) in patients with COPD combined with CVD. Methods: Fifty one stable patients with COPD were enrolled (25 COPD, 26 COPD + CVD). Lung function, sputum, peripheral blood samples, serum H2S, Hcy, high-sensitivity C-reactive protein (hs-CRP) and tumor necrosis factor-α (TNF-α) levels were measured. Dyspnea, symptoms and quality of life were quantified by modified Medical Research Council dyspnea scale (mMRC), COPD assessment test (CAT) and St. George’s Respiratory Questionnaire (SGRQ). Results: Compared with COPD group, waist circumference and body mass index (BMI) were higher in COPD + CVD group, mMRC, CAT and activity scores were also higher, high density lipoprotein cholesterol (HDL-C) was lower, total cells, neutrophils (%) in sputum and serum hs-CRP level were higher, whereas macrophages (% ) in sputum was lower. H2S and Hcy levels from COPD + CVD group were higher than those from COPD group, but H2S/Hcy ratio was lower. With increasing COPD severity, H2S level was decreased, however, Hcy level was increased. H2S level was positively correlated with FEV1/FVC, FEV1% predicted, lymphocytes (%) and macrophages (%) in sputum, but negatively correlated with smoking pack-years and neutrophils (%) in sputum. Hcy level was positively correlated with BMI and total cells in sputum. The ratio of H2S/Hcy was also positively correlated with FEV1/FVC, but negatively correlated with total cells in sputum. Conclusion: The imbalance of H2S/Hcy may be involved in the pathogenesis of COPD combined with CVD and provide novel targets for therapy.